Emergency medicine: what keeps me, what might lose me? A narrative study of consultant views in Wales. Issue 7 (29th March 2017) - James, Ffion; Gerrard, Frances
Abstract : EDs are currently under intense pressure due to increased patient demand. There are major issues with retention of senior personnel, making the specialty a less attractive choice for junior doctors. This study aims to explore what attracted EM consultants to their career and keeps them there. It is hoped this can inform recruitment strategies to increase the popularity of EM to medical students and junior doctors, many of whom have very limited EM exposure. Methods: Semistructured interviews were conducted with 10 consultants from Welsh EDs using a narrative approach. Results: Three main themes emerged that influenced the career choice of the consultants interviewed: (1) early exposure to positive EM role models; (2) non-hierarchical team structure; (3) suitability of EM for flexible working. The main reason for consultants leaving was the pressure of work impacting on patient care. Conclusion: The study findings suggest that EM consultants in post are positive about their careers despite the high volume of consultant attrition. This study reinforces the need for dedicated undergraduate EM placements to stimulate interest and encourage medical student EM aspirations. Consultants identified that improving the physical working environment, including organisation, would increase their effectiveness and the attractiveness of EM as a long-term career.